COach2Quit: A Pilot Randomized Controlled Trial of a Personal Carbon Monoxide Monitor for Smoking Cessation. Issue 11 (29th August 2018) - Krishnan, Nandita; Elf, Jessica L; Chon, Sandy; Golub, Jonathan E
Abstract: Introduction: Mobile phone–based messaging support and biomarker feedback independently show evidence of increasing an individual's likelihood of quitting smoking. However, the combination of these two strategies to facilitate smoking cessation has not been adequately explored. Methods: We conducted a randomized controlled trial in Baltimore, Maryland, to assess the efficacy of COach2Quit, a smartphone application that provides exhaled carbon monoxide readings with message support. The primary outcome was self-reported and biochemically verified smoking cessation at 30-day follow-up. Secondary outcomes were reduction in smoking, motivation to quit, and engagement and satisfaction with COach2Quit. An intention-to-treat analysis was conducted. Results: Adult smokers were randomized 1:1 to receive brief advice and COach2Quit (intervention, n = 50) or brief advice only (control, n = 52). Thirteen participants were lost to follow-up. At 30-day follow-up, one participant in each arm quit smoking. Median change in carbon monoxide levels (in parts per million (ppm)) (intervention: −3.0 [interquartile range (IQR) −12.0, 2.0]; control: −2.5 [IQR −9.0, 2.0]) and median change in number of cigarettes smoked per day (intervention: −5.5 [IQR −14.0, −1.0]; control: −6.0 [IQR −10.0, −2.0]) was similar between study arms. There was no significant difference in mean percent change in the Reasons for Quitting scale score (intervention: 6.3 [95% confidence interval = −2.2% to 14.8%]; control: −3.6 [95% confidence interval = −9.2% to 2.1%]). A majority ( n = 32, 91%) of participants liked having COach2Quit to help them quit smoking. Conclusions: There were no significant differences in smoking cessation, smoking reduction, and motivation to quit between study arms. However, high satisfaction with the COach2Quit application indicates its feasibility and acceptability as a smoking cessation tool. Implications: Smoking is the leading preventable cause of morbidity and mortality in the United States. Although counseling and pharmacotherapy are efficacious for smoking cessation, they are not easily accessible or desirable to all smokers, highlighting the need for identifying other interventions. There is evidence for the efficacy of mobile phone–based messaging support for smoking cessation. However, there is limited research on the efficacy of biomarker feedback, much less interventions that combine these two approaches. This research contributes to filling this gap and identifying novel interventions to facilitate smoking cessation.